2020
DOI: 10.1021/acs.jpclett.0c01169
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Single-Molecule Dynamics and Biological Functions of Antimicrobial Peptide Melittin

Abstract: Many fundamental biological processes occur on cell membranes, and a typical example is the membrane permeabilization by peptides for an antimicrobial purpose. Previous studies of the underlying mechanism mostly focus on structural changes of membranes and peptides during their interactions. Herein, from a new perspective of single-molecule dynamics, the real-time three-dimensional motions of individual phospholipid and peptide molecules were monitored, and specifically, their correlation with the membrane por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 48 publications
0
33
0
Order By: Relevance
“…After that, a high-quality SLB was formed. 32 The silicon-supported SPB was immediately moved to and installed in the photo-voltage test system and worked as a working electrode in the following tests (with a working area of 15 Â 10 mm 2 ). Before each test, the voltage pulses under light illumination of electrodes immersed in deionized water were recorded first, as a baseline for the following in situ test.…”
Section: Setup Of the Photo-voltage Monitoring Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…After that, a high-quality SLB was formed. 32 The silicon-supported SPB was immediately moved to and installed in the photo-voltage test system and worked as a working electrode in the following tests (with a working area of 15 Â 10 mm 2 ). Before each test, the voltage pulses under light illumination of electrodes immersed in deionized water were recorded first, as a baseline for the following in situ test.…”
Section: Setup Of the Photo-voltage Monitoring Systemmentioning
confidence: 99%
“…This phenomenon is similar as that of many antimicrobial peptides (e.g., melittin, PGLa and Magainin) at low concentrations. 29,32 In brief, photovoltage and GUV leakage tests showed that, at low concentrations (e.g., 1-10 mM), TTAB produced an obvious while concentrationdependent permeabilization effect on the phospholipid membrane which reached equilibrium within minutes; however, this effect became complicated (e.g., at 10 mM) due to the coexistence of many competitive processes.…”
Section: The Membrane Actions Of Ttab At Low Concentrations (R10 Lm)mentioning
confidence: 99%
“…For Mel, its crystal structure was taken from the protein data bank (PDB ID: 2MLT). Specifically, chain A, which has a more flexible structure and consequently an improved membrane activity, was chosen (Irudayam and Berkowitz, 2012;Lyu et al, 2017;Deng et al, 2019;Xu et al, 2020). Then the peptide was coarse-grained using the Martinize script with MARTINI force field (version 2.2) (de Jong et al, 2013;Deng et al, 2019;Marrink et al, 2007).…”
Section: Simulation Modelsmentioning
confidence: 99%
“…As a result of the complicated Mel-lipid interactions, to form transmembrane pores is a premise of the function realization of Mel (Hong et al, 2019;Lee et al, 2013;Krauson et al, 2012). Such an interaction process generally obeys the two-state model, including the binding and accumulation of peptides on membrane surface and the subsequent transmembrane insertion of peptides for pore formation (Huang, 2000;Lee et al, 2013;Xu et al, 2020). This process is influenced by many factors especially the peptide concentration, i.e., the peptide-to-lipid ratio, P/L (Hong et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation